Multicomponent, Solvent-Free Synthesis of 1-Amidoalkyl-2-naphthols in the Presence of H3+xPMo12-x Vx O40 Heteropolyacids as Recyclable and Green Catalysts. Issue 2 (2011) - Bamoharram, Fatemeh F.; Heravi, Majid M.; Roshani, Mina; Charkhi, Mohammad J. Sane
Abstract : A rapid and efficient one-pot method for the synthesis of 1-amidoalkyl-2-naphthols has been developed in the presence of mixed-addenda vanadium(V)-substituted polyoxomolybdates including: H3+x PMo12-x Vx O40 (x=1-3) heteropolyacids (HPAs) as recyclable catalysts under solvent-free conditions. In all cases heteropolyacid with x = 3 gave the highest yield under solvent-free conditions.